Economic Valuation of Maria Tritis Cave Tourism - Rahmat Slamet Suyoto; Sudiman Sudiman; Aulia Izzafathih; Renoldi Elya Sermeha; Prayuda Gita Rizkitama (Global Health Science Group, 2026)
The purpose of this research is to estimate the potential value of Maria Tritis Cave using the Individual Travel Cost Method and to identify the factors influencing visitor rates to the cave. Applying statistical methode to acces tool validity and reliability the quantitative method was used, and primary data was collected through we have simple random sampling technic a questionnaire from 100 people who had visited or were visiting the cave. SPSS 26 software was employed for data analysis, which included multiple linear regression. According to the findings, travel cost and visitors’ age have an impact on the number of visitors to Maria Tritis Cave, while income and distance do not. The average visitor surplus per visit is Rp84,581, and the economic value of Maria Tritis Cave in 2022 is Rp3,287,558,656.